Great-Rag-Sketches, Source Study for Stravinsky's Piano-Rag-Music - Gordon, Tom (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2005)
Sketches, drafts and the composer's fair copy for Piano-Rag-Music are explored in this study of Stravinsky's compositional process during his early neo-classicism. These autographs reveal the composers starting materials, his working methods, the weight of his compositional preoccupations and the surprising conditions of assemblage of the work. Further, they confirm that the three distinct elements fused by hyphen in the works title do indeed define both the works content and objective. Virtuoso pianism and the rhythmic vitality of ragtime improvisation are synthesized in a pure music form that is neither conventional nor hybrid, but an outgrowth of the materials themselves.